2019
DOI: 10.1016/j.ajo.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Bevacizumab for Tractional Retinal Detachment in Proliferative Diabetic Retinopathy: A Prospective Randomized Clinical Trial

Abstract: PURPOSE: To assess the effectiveness and safety of an intravitreal injection of 1.25 mg bevacizumab (IVB) as a preoperative adjunct to small-gauge pars plana vitrectomy (PPV) compared with PPV alone in eyes with tractional retinal detachment secondary to proliferative diabetic retinopathy.METHODS: This prospective, double-masked, randomized, multicenter, active-controlled clinical trial enrolled 224 eyes of 224 patients between November 2013 and July 2015. All eyes underwent a baseline examination including be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 33 publications
(44 reference statements)
2
44
0
Order By: Relevance
“…neovascularization leads to vitreous opacity, retinal proliferative membrane occurrence, retinal traction detachment and impaired visual function (19). Furthermore, intraoperative bleeding affects the surgical field and prolongs the operation time (23). The present results demonstrated that intraoperative bleeding was reduced in the combined drug treatment group during the PPV operation compared with that in the simple surgery group due to the reduced number of new blood vessels in the neovascular proliferation membrane of patients.…”
Section: Discussionmentioning
confidence: 57%
“…neovascularization leads to vitreous opacity, retinal proliferative membrane occurrence, retinal traction detachment and impaired visual function (19). Furthermore, intraoperative bleeding affects the surgical field and prolongs the operation time (23). The present results demonstrated that intraoperative bleeding was reduced in the combined drug treatment group during the PPV operation compared with that in the simple surgery group due to the reduced number of new blood vessels in the neovascular proliferation membrane of patients.…”
Section: Discussionmentioning
confidence: 57%
“…The decision of whether to treat an eye with bevacizumab prior to surgery is primarily a surgeon preference (SSRI, CJ); intravitreal administration of bevacizumab prior to surgery decreases intra-operative bleeding and makes surgical dissection of tractional membranes less difficult [ 9 ]. Thus, pre-treatment of diabetic tractional retinal detachments can help improve surgical outcomes, especially with very complex tractional detachments [ 9 , 39 ]. This is the primary reason why so few samples were not treated with bevacizumab prior to surgery were available for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic TRDs (ie, >6 months) involving the macula may also benefit from surgery, but the visual prognosis remains guarded. Pre‐operative anti‐VEGF reduces the duration of vitrectomy and intraoperative and postoperative complications, including retinal breaks 90,91 . The surgical management of diabetic TRDs will not be covered in this review.…”
Section: Current Recommendations For Diabetic Eye Disease Managementmentioning
confidence: 99%
“…Pre-operative anti-VEGF reduces the duration of vitrectomy and intraoperative and postoperative complications, including retinal breaks. 90,91 The surgical management of diabetic TRDs will not be covered in this review.…”
Section: Proliferative Diabetic Retinopathymentioning
confidence: 99%